Semi-dependent self-employment under conditions characteristic of the employment relationship - Kobroń-Gąsiorowska, Łucja (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The expansion of non-standard forms of work-self-employment or work through online platforms-has created competition between the traditional contract labor model and the non-standard form, which also creates an employee-employer relationship. This article aims to suggest a different, complementary rather than antagonistic relationship between employment and labor law. However, I state that it is only a prelude to the polemic that is about to begin. In this article, I examine the legal construction of the relationship between traditional contract employment and semi-independent self-employment, which is based on the conceptualization of these two forms of labor as separate and at the same time having in common the labor entitlements derived from the principle of decent work.